Influence of wear and tool geometry on the chatter, cutting force, and surface integrity of TB6 titanium alloy with solid carbide cutters of different geometry - Liu, Jianyong (Strojniški vestnik, 2020)
In this paper, vibration-free milling cutters (variable helix (VH) and variable pitch (VP) end mills) and standard (SD) end mills are used to machine TB6 (Ti-10V-2Fe-3Al) titanium alloy in order to study the influence of wear and geometric structure parameters of milling cutters on chatter, cutting force and surface integrity of machined surfaces. The results of the tests show that the wear of milling cutters has a significant influence on the chatter, cutting force, roughness, residual stress, and microhardness. Geometric structure parameters of milling cutters also have a clear impact on both chatter and cutting force. Also, chatter and cutting force have significant effects on roughness and residual stress, which are in turn affected by tool geometric structure parameters, separately.
Keywords: chatter; cutting force; drdranje; integriteta površin; obraba; rezalne sile; surface integrity; TB6 Titanium alloy; titanova zlitina TB6; wear